Construção de um programa de ensino de pré-requisitos de leitura e escrita para pessoas com deficiência intelectual - Freitas, Maria Clara de (Universidade Federal de São Carlos, 2012)
Since its dawn, Behavior Analysis stood out in the search for ways of teaching complex repertoires to persons with intellectual retardation. Procedures built on stimulus equivalence have proved highly effective and economical, especially with regard to academic and symbolic skills. In Brazil, there is a tradition of successful research concerning the teaching of reading and spelling skills for children with learning disabilities. One of these computer presented procedures has recently been adapted for application to children with intellectual retardation, with excellent results, similar to those encountered by previous studies with other populations. However, to initiate the training in reading, based upon arbitrary MTS and CRMTS tasks, those children had to show a series of prerequisites skills, skills which commonly are to be found missing on people with higher levels of intellectual disabilities. It is urgent, then, to insert the teaching of those skills in the programs, so that more children can benefit from the reading instruction. The objectives of this study were: to identify which prerequisite skills are necessary for teaching reading based on a behavior network; to verify which strategies would be needed to teach such skills to students witch deficits in those repertoires, and finally, to build as a final product a comprehensive education program, to meet the difficulties of the largest possible number of students with intellectual disabilities. Four consecutive studies were designed, pursuing these goals. The first study investigated the possibility of building such a teaching program for prerequisites based on the strategies used by the regular reading program (CRMTS and MTS), and its results showed a relative success to the four participants. Study 2, attempting to expand the strategies to teach prerequisites skills, enrolled three other students in a new learning program, now using techniques such as Observing Response and Fading, and a new strategy, called Dragging-to-Sample. Its data showed higher rates of success, supporting the decision to introduce the new strategies, although flaws in the programming show a possible lack of control. Thus, Study 3 was implemented aiming to correct those flaws, in addition to program the teaching of new skills to the same three children from Study 2 and two other new students. Their positive results showed that the teaching programs successful taught the prerequisites for all but one student. Finally, Study 4 gathered all students who had finished the procedures from previous Studies, and its goal was to enroll them on the reading program, to thus verify the effectiveness and adequacy of the prerequisite programs built here. Their positive results indicated that the teaching programs actually taught the necessary prerequisites for students to enroll on a reading program. The data also clearly show the superiority of the last teaching program (Study 3) when compared to the first program (Study 1), corroborating both the prerequisite skills and support strategies chosen. The final product of the four studies was a prerequisite teaching program which could effectively help children with intellectual disabilities to achieve higher levels of reading comprehension.
Development of program to teach reading and spelling prerequisites for students with intellectual disabilities
Keywords: Behaviorismo (Psicologia); Deficiência intelectual; Ensino de pré-requisitos; Leitura e Escrita; Programação de ensino; Análise do Comportamento; Educação especial; Intellectual disabilities; Pre-requisites; Read and Spelling; Programmed Teaching; CIENCIAS HUMANAS::PSICOLOGIA